The “Other” in Court: Islam and Muslims in Polish Judicial Opinions Published Online - Górska, Ewa; Juzaszek, Anna (International journal for the semiotics of law = Revue internationale de sémiotique juridique, 2023)
Muslims are a marginal minority in Poland, but research shows that they are often subject to negative perceptions and hostility from the majority. Orientalist stereotypes about Islam and the people associated with it are widespread and often reproduced in the media. Research from North America and the European Court of Human Rights suggests that such prejudices can affect the adjudication of cases involving Muslims. It may be presumed that Poland is no exception to that, and this assumption was the starting point for our empirical study. To date, there have been no studies on the perception of Muslims and Islam in the Polish legal system. This article presents the results of a qualitative thematic analysis of 57 judicial opinions issued by the common courts in Poland and published online, in which Islam or being Muslim was mentioned. The cases were categorised and texts of the judicial opinions closely analysed (with computer-assisted qualitative data analysis software) to identify recurring themes. The findings of this first exploratory study show that stereotypical representations and the “‘Othering” of Muslims do indeed occur in Polish courts, with some judges repeating Orientalist tropes that have become normalised in Polish society.